2007
DOI: 10.1159/000108111
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Neurodegenerative Disease and Exposure to Extremely Low-Frequency Magnetic Fields: 31 Years of Observations on Swiss Railway Employees

Abstract: Aims: The objective of the present study was to investigate the relationship between extremely low-frequency magnetic field (ELF-MF) exposure and mortality from several neurodegenerative conditions in Swiss railway employees. Methods: We studied a cohort of 20,141 Swiss railway employees with 464,129 person-years of follow-up between 1972 and 2002. For each individual, cumulative exposure was calculated from on-site measurements and modelling of past exposure. We compared cause-specific mortality in highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 48 publications
1
39
0
1
Order By: Relevance
“…In this study, the lack of association between occupational physical activity and the absence of a dose-response relationship supports the hypothesis that increasing ALS susceptibility is not increased exclusively by physical activity but rather also by genetic profile or life habits [61]. Exposure to electromagnetic fields has been studied in epidemiological [62][63][64][65][66], observational [67] and laboratory works [68]. A recent meta-analysis suggests a slightly but significantly increased risk of ALS among workers exposed to an extremely low frequency electromagnetic field (ELF-EMF), but does not deny the possibility of bias in the data analysis [69].…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the lack of association between occupational physical activity and the absence of a dose-response relationship supports the hypothesis that increasing ALS susceptibility is not increased exclusively by physical activity but rather also by genetic profile or life habits [61]. Exposure to electromagnetic fields has been studied in epidemiological [62][63][64][65][66], observational [67] and laboratory works [68]. A recent meta-analysis suggests a slightly but significantly increased risk of ALS among workers exposed to an extremely low frequency electromagnetic field (ELF-EMF), but does not deny the possibility of bias in the data analysis [69].…”
Section: Discussionsupporting
confidence: 72%
“…Other studies on multiple sclerosis mostly found no evidence of an association (Feychting et al 2003;Håkansson et al 2003;Röösli et al 2007;Vergara et al 2013), while Li et al (2008) found a slightly elevated RR for electrical workers (RR 1.33, 95% CI 0.85-1.98) in a Swedish cohort study.…”
Section: Comparison With Previous Follow-ups In the Cohort And Othermentioning
confidence: 76%
“…Exposure to electromagnetic fields was addressed in two case-control studies (48,53) and eight register/cohort studies (25,34,39,40,49,51,54,57). The weighted RR was 1.07 (95% CI 0.97-1.19).…”
Section: Electromagnetic Fields and Work With Electricitymentioning
confidence: 99%